The Impact Of Service Quality On Loyalty Intention And Customer Satisfaction: The Moderating Effect Of Price Fairness And Switching Cost Of Prepaid Mobile Phone Users In Thailand - Srikanjanarak, Saowanee (2010)

(untitled)
Increasing global competition has led to an intensively competitive market among service providers. Several organizations have created and developed a variety of products or services; in particular the telecommunications industry has developed mobile phone services. Various value-added services linked to mobile phone services, the complexity of price strategies in mass service context is increasingly competitive, offering variety of service options among service providers and various promotions have been increasingly used as major tools to retain their existing customers.